Ex utero intrapartum therapy in infants with congenital diaphragmatic hernia: a propensity score matching analysis - Chao Liu; Ying Wang; Feng Feng; Shan Jian; Hua Meng; Yunlong Zhao; Lijian Pei; Yulin Jiang; Yandong Wei; Xiting Zhu; Xiaochen Bai; Yan Lv; et al. (BMJ Publishing Group, 2022)
Objective Previous studies have shown that ex utero intrapartum therapy (EXIT) is safe and feasible for newborns with congenital diaphragmatic hernia (CDH). This study reports our experience with EXIT in fetuses with CDH in an attempt to explore the efficacy of EXIT on the survival rate of this population.Methods A retrospective analysis of the clinical data of 116 children with CDH was conducted. The children were assigned to EXIT and non-EXIT groups. Propensity score matching (PSM) toward clinical data was performed, and the clinical characteristics and outcomes were compared. Taking survival at discharge as the main outcome, logistic regression analysis was carried out to explore the efficacy of EXIT on survival.Results During the study period, 30 of 116 children received EXIT. After PSM, the survival rates of the EXIT group and the non-EXIT group were 82.76% (24/29) and 48.28% (14/29), respectively (p=0.006). EXIT (OR=0.083, 95% CI=0.013to 0.525, p=0.008), liver herniation (OR=16.955, 95% CI=2.342 to 122.767, p=0.005), and gestational age at diagnosis (OR=0.662, 95% CI=0.497 to 0.881, p=0.005) were independent mortality-related risk factors of all children with CDH. Ninety-nine of 116 children underwent surgery. After PSM, the postoperative survival rates of the EXIT group and non-EXIT group were 84.6% (22/26) and 76.9% (20/26), respectively (p=0.754). Liver herniation (OR=10.451, 95% CI=1.641 to 66.544, p=0.013) and gestational age at diagnosis (OR=0.736, 95% CI=0.577 to 0.938, p=0.013) were independent mortality-related risk factors of children after surgery.Conclusion EXIT can be performed safely for selected prenatally diagnosed CDH neonates with potentially better survival and does not cause more maternal complications compared with traditional cesarean section.